INVENTARISASI TUMBUHAN PAKAN LEBAH MADU HUTAN DI DESA UJUNG JAYA KAWASAN TAMAN NASIONAL UJUNG KULON - Nuniek Hermita (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
Objective of this research was to identify plant potential as woof source of forest honeybee so woof that produce honey quality and quantity from forest honey bee is available and to identify participation of people around Ujung Kulon national park in guarding and conserving woof source plant for forest honeybee. It was survey research with quantitative method combined with qualitative method. It was conducted by taken sample of one population, to collect data. Information was analyzed qualitatively to obtain clear description on research result. To answers potential of woof plant for forest honeybee it used vegetation analysis and to measure people participation in Ujung Jaya village around Ujung Kulon national park in guarding and conserving plant of woof source for forest honeybee it used quantitative descriptive analysis it used non parametric statistic of Spearman rank correlation. The result indicate that it has been identified in field nine plant species as woof source of forest honeybee in the research site either cultivated or non cultivated by people in the area. Plants as woof source are Salam, Sigeung, Samangan, Kawai, Kijahe, Kiganik, Padipadi, Lame and Tongtolok. Based on spearman rank correlation test, participation level of people around Ujung Kulon national park in guarding and conserving woof source plant for forest honeybee correlate to respondent income with coefficient of 0.267*. The correlation score indicated strong association with people participation or has significant effect. Meanwhile, age and education level indicated weak association or no significant effect.